Optimizing DNA hypomethylating therapy in acute myeloid leukemia and myelodysplastic syndromes. (31st August 2021) - Straube, Jasmin; Lane, Steven W.; Vu, Therese
Abstract: The DNA hypomethylating agents (HMA) azacitidine (AZA) and decitabine (DAC) improve survival and transfusion independence in myelodysplastic syndrome (MDS) and enable a low intensity cytotoxic treatment for aged AML patients unsuitable for intensive chemotherapy, particularly in combination with novel agents. The proposed mechanism of AZA and DAC relies on active DNA replication and therefore patient responses are only observed after multiple cycles of treatment. Although extended dosing may provide the optimal scheduling, the reliance of injectable formulation of the drug limits it to intermittent treatment. Recently, an oral formulation of AZA demonstrated significantly improved patient relapse free survival (RFS) and overall survival (OS) when used as maintenance after chemotherapy for AML. In addition, both DAC and AZA were found to be highly effective to improve survival in elderly patients with AML through combination with other drugs. These recent exciting results have changed the therapeutic paradigm for elderly patients with AML. In light of this, we review current knowledge on HMA mechanism of action, clinical trials exploring dosing and scheduling, and recent HMA combination therapies to enhance efficacy. Abstract : DNA hypomethylating agents (HMA) are a promising treatment alternative to chemotherapy for elderly patients with myelodysplastic syndrome (MDS) or acute myeloid leukemia (AML). This article summarizes key progress made on HMA research including proposed mechanisms, optimal scheduling and dosing, and clinical trials of combination therapies.